"Local determination", even if we could find it, does not challenge free will: Commentary on Marcelo Fischborn. (17th February 2017) - Roskies, Adina; Nahmias, Eddy
Abstract: Marcelo Fischborn discusses the significance of neuroscience for debates about free will. Although he concedes that, to date, Libet-style experiments have failed to threaten "libertarian free will" (free will that requires indeterminism), he argues that, in principle, neuroscience and psychology could do so by supporting local determinism. We argue that, in principle, Libet-style experiments cannot succeed in disproving or even establishing serious doubt about libertarian free will. First, we contend that "local determination", as Fischborn outlines it, is not a coherent concept. Moreover, determinism is unlikely to be established by neuroscience in any form that should trouble compatibilists or libertarians—that is, anyone who thinks we might have free will. We conclude that, in principle, neuroscience will not be able undermine libertarian free will and explain why these conclusions support a coherent compatibilist notion of causal sourcehood.